The arthritis severity locus Cia5a regulates the expression of inflammatory mediators including Syk pathway genes and proteases in pristane-induced arthritis - Brenner Max; Gulko Pércio S (BMC Genomics, 2012)
Abstract Background Cia5a is a locus on rat chromosome 10 that regulates disease severity and joint damage in two models of rheumatoid arthritis, collagen- and pristane-induced arthritis (PIA). In this study, we aimed to identify cellular and molecular processes regulated by Cia5a using microarray-based gene expression analysis of synovial tissues from MHC identical DA (severe erosive disease) and DA.F344(Cia5a) congenics (mild non-erosive disease) rats. Results Synovial tissues from six DA and eight DA.F344(Cia5a) rats were analyzed 21 days after the induction of PIA using the Illumina RatRef-12 BeadChip (21,922 genes) and selected data confirmed with qPCR. There was a significantly increased expression of pro-inflammatory mediators such as Il1b (5-fold), Il18 (3.9-fold), Cxcl1 (10-fold), Cxcl13 (7.5-fold) and Ccl7 (7.9-fold), and proteases like Mmp3 (23-fold), Mmp9 (32-fold), Mmp14 (4.4-fold) and cathepsins in synovial tissues from DA, with reciprocally reduced levels in congenics. mRNA levels of 47 members of the Spleen Tyrosine Kinase (Syk) pathway were significantly increased in DA synovial tissues compared with DA.F344(Cia5a), and included Syk (5.4-fold), Syk-activating receptors and interacting proteins, and genes regulated by Syk such as NFkB, and NAPDH oxidase complex genes. Nuclear receptors (NR) such as Rxrg, Pparg and Rev-erba were increased in the protected congenics, and so was the anti-inflammatory NR-target gene Scd1 (54-fold increase). Tnn (72-fold decrease) was the gene most significantly increased in DA. Conclusions Analyses of gene expression in synovial tissues revealed that the arthritis severity locus Cia5a regulates the expression of key mediators of inflammation and joint damage, as well as the expression of members of the Syk pathway. This expression pattern correlates with disease severity and joint damage and along with the gene accounting for Cia5a could become a useful biomarker to identify patients at increased risk for severe and erosive disease. The identification of the gene accounting for Cia5a has the potential to generate a new and important target for therapy and prognosis.